Contemporary Outcomes After Partial Resection of Infected Aortic Grafts - Janko, Matthew; Hubbard, Grant; Woo, Karen; Kashyap, Vikram S.; Mitchell, Megan; Murugesan, Arun; Chen, Lin; Gardner, Rachel; Baril, Donald; Hacker, Robert I.; Szeberin, Zoltan; ElSayed, Ramsey; et al. (Elsevier, 2021)
Introduction: Aortic graft infection remains a considerable clinical challenge, and it is unclear which variables are associated with adverse outcomes among patients undergoing partial resection. Methods: A retrospective, multi-institutional study of patients who underwent partial resection of infected aortic grafts from 2002 to 2014 was performed using a standard database. Baseline demographics, comorbidities, operative, and postoperative variables were recorded. The primary outcome was mortality. Descriptive statistics, Kaplan-Meier (KM) survival analysis, and Cox regression analysis were performed. Results: One hundred fourteen patients at 22 medical centers in 6 countries underwent partial resection of an infected aortic graft. Seventy percent were men with median age 70 years. Ninety-seven percent had a history of open aortic bypass graft: 88 (77%) patients had infected aortobifemoral bypass, 18 (16%) had infected aortobiiliac bypass, and 1 (0.8%) had an infected thoracic graft. Infection was diagnosed at a median 4.3 years post-implant. All patients underwent partial resection followed by either extra-anatomic (47%) or in situ (53%) vascular reconstruction. Median follow-up period was 17 months (IQR 1, 50 months). Thirty-day mortality was 17.5%. The KM-estimated median survival from time of partial resection was 3.6 years. There was no significant survival difference between those undergoing in situ reconstruction or extra-anatomic bypass (P = 0.6). During follow up, 72% of repairs remained patent and 11% of patients underwent major amputation. On univariate Cox regression analysis, Candida infection was associated with increased risk of mortality (HR 2.4; P = 0.01) as well as aortoenteric fistula (HR 1.9, P = 0.03). Resection of a single graft limb only to resection of abdominal (graft main body) infection was associated with decreased risk of mortality (HR 0.57, P = 0.04), as well as those with American Society of Anesthesiologists classification less than 3 (HR 0.35, P = 0.04). Multivariate analysis did not reveal any factors significantly associated with mortality. Persistent early infection was noted in 26% of patients within 30 days postoperatively, and 39% of patients were found to have any post-repair infection during the follow-up period. Two patients (1.8%) were found to have a late reinfection without early persistent postoperative infection. Patients with any post-repair infection were older (67 vs. 60 years, P = 0.01) and less likely to have patent repairs during follow up (59% vs. 32%, P = 0.01). Patients with aortoenteric fistula had a higher rate of any post-repair infection (63% vs. 29%, P < 0.01) Conclusion: This large multi-center study suggests that patients who have undergone partial resection of infected aortic grafts may be at high risk of death or post-repair infection, especially older patients with abdominal infection not isolated to a single graft limb, or with Candida infection or aortoenteric fistula. Late reinfection correlated strongly with early persistent postoperative infection, raising concern for occult retained infected graft material.